PRODUCTIVE PERFORMANCE AND SOME CARCASS CHARACTERISTICS OF AWASSI LAMBS FED ON DIFFERENT LEVELS OF FAT FROM POULTRY SLAUGHTERHOUSES - Ahmed Hussein kutta; Mahfoodh Kaleel Abdullah; Prof. Dr. Mahfoodh Kaleel Abdullah (Scholar Express Journals, 2023)
The study aimed to follow up the treatments added to the fat of poultry slaughterhouse and their impact on improving some productive performance and some meat characteristics in male Awassi lambs, the weight of the animals was recorded weekly for the duration of the study (120 days), all lambs were slaughtered, skinned and hollowed until the end of the study period and the results were as follows: where the treatments T3 and T4 outperformed a high significant superiority
Keywords: fat poultry slaughterhouse; lamb growth; Rumen fermentation and Carcass Characteristics